(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
The demand in an efficient technique to monitor the condition of the pipeline for oil and gas industries leads to research into alternative solutions. The conventional methods are often too expansive and require manpower to conduct an on-site inspection. Using the Eddy current testing as the main principle, this study aims to explore the capability of 8-coil channel EMT as pipeline imaging in a different analytical situation. The 2D 8-coil channel is developed using COMSOL Multiphysics and using 20 kHz sinusoidal frequency to detect the pipeline with different materials, which is alloy and aluminum. Simulation results proved that EMT is a capable tool for inspection of metallic pipelines. This paper also presented a comparison of the pipeline cross-sectional images from the simulation and experimental.